First Corinthians : a new translation with introduction and commentary - Fitzmyer, Joseph A. (Bible., 2008)
In this volume, Joseph A. Fitzmyer provides a new commentary on one of the most important and beloved books of the Bible. A biblical masterpiece and a seminal contribution to Christian theology, First Corinthians was written by St. Paul to the congregation at Corinth in response to a letter asking him for clarification of some of his teachings. In it, Paul discusses the basic tenets of Christian faith, including the Lord's Supper and the Resurrection, and addresses questions about marriage, celibacy, and other down-to-earth matters of moral conduct and Christian living. It also contains Paul's memorable definition of Christian love.